Lei de anistia e justiça de transição brasileira: análise da legitimidade de seus instrumentos Jurídicos - Bernardo Segundo, Ronaldo Louzada (2012)
The objective of this paper is to discuss the democratic legitimacy of a legal instrument on the political transition that took place after the last dictatorship period lived in Brazil, between the years 1964 and 1985, approaching from the theoretical framework established by Friedrich Müller, in "Who are the people?", the validity of the Brazilian Amnesty Law. Based on the analysis of the essential concepts to understanding the subject, such as amnesty, transitional justice and political crimes, discusses the different historical experiences lived on different countries to demonstrate the diversity of solutions to address the questions posed by the need for political transition societies different from its historical, cultural and political and thereby demonstrate that the solution found by the Brazilian society, when his last political transition is the result of its peculiarities, not deserving reproach from the comparison with other solutions found by other societies.